Aluminum alloy material, battery shell and power battery
By adding Ce elements to aluminum alloy materials and optimizing the material structure, the problem of structural instability of the power battery shell in extreme environments is solved, and its heat resistance and structural strength are significantly improved, ensuring the performance in harsh environments and Security.
Patent Information
- Application Number
- CN202411716477.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-11
AI Technical Summary
It is difficult for existing aluminum alloy materials to maintain structural stability in extreme environments, resulting in the performance and service life of the power battery shell in high temperature and high humidity, plateau and high cold environments.
By adding a specific content of Ce element to the aluminum alloy material, a stable heat-resistant phase is formed, and the high-temperature resistance of the material is enhanced by refining the grains and improving the microhardness. At the same time, by controlling grain size and distribution, as well as aging treatment, the microstructure of the material is optimized, and the elastic modulus and fatigue resistance are improved.
The heat resistance and structural strength of the power battery case are significantly improved, so that it maintains structural stability in complex environments, extends the thermal deformation cycle, improves structural strength and fatigue resistance, and enhances adaptability and safety to extreme environments.
Smart Images

Figure CN119410967A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum alloy materials, and in particular to an aluminum alloy material, a battery casing and a power battery. Background Art
[0002] The rapid development of the new energy vehicle industry has put forward higher requirements on the performance of power batteries, especially stability and safety in extreme environments. During the charging and discharging process of power batteries, the thermal expansion and contraction of battery components will cause the shell to deform. This deformation is particularly significant in harsh environments such as high temperature and humidity, high altitude and high cold, which seriously affects the performance and service life of the battery. Therefore, improving the heat resistance and structural strength of the power battery shell has become the key to the current technological development.
[0003] Aluminum alloys are widely used in power battery housings due to their light weight, corrosion resistance and excellent mechanical properties. However, the protection effect of existing aluminum alloys in special operating environments, such as charge and discharge cycles and extreme climatic conditions, needs to be improved. In particular, the performance of existing materials still has room for improvement in terms of improving structural stiffness, bending limit, pressure resistance limit and thermal attenuation gradient.
[0004] To meet these needs, the present invention proposes a new aluminum alloy material and a preparation method thereof, which aims to significantly improve the heat resistance and structural strength of the power battery housing by optimizing the material composition and heat treatment process. By adding specific alloying elements such as cerium, copper or magnesium, a stable heat-resistant phase is formed, and the high temperature resistance of the material is enhanced by refining the grains and increasing the microhardness. At the same time, by controlling the grain size and distribution, and optimizing the microstructure of the material through aging treatment, the elastic modulus and fatigue resistance of the aluminum alloy are improved, thereby enhancing the structural rigidity and bending limit of the housing.
[0005] These technical optimizations will enable the power battery housing to maintain structural stability under high temperature conditions, extend the thermal deformation cycle, increase the softening temperature and reduce the softening degree, while improving its structural strength and fatigue resistance, making it more adaptable and safe in complex use environments. This is crucial to ensure the performance and safety of new energy vehicle power batteries in harsh environments such as high temperature and humidity, high altitude and high cold. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the technical problem to be solved by the present invention is to provide an aluminum alloy material with better strength, and to provide a battery casing and a power battery containing the material.
[0007] In order to solve the above technical problems, a technical solution adopted by the present invention is: a first aspect is provided
[0008] An aluminum alloy material comprises at least Al, Mn, Si, Cu, Fe and Ce, wherein the mass percentage of Ce is 0.3-1wt%.
[0009] This application starts from the purpose of improving the strength of aluminum alloys, and adds a specific amount of Ce as a raw material into aluminum alloys for modification. On the one hand, because Ce is a rare earth element with a large atomic radius, which is much larger than the atomic radius of Al, it can bear the nucleation point in the melt, increase the nucleation concentration during solidification, and has a strong ability to refine grains. It can refine grains, improve mechanical strength and microhardness of the organization, and increase the elastic modulus, thereby improving the structural rigidity of the battery shell and ensuring the life of lithium batteries at 100 degrees Celsius. 2500-3000 breathing cycles. Compared with low-multiple organizations without adding Ce elements, it can reduce aluminum grains by one-half to one-third, which can refine grains and effectively hinder the movement of dislocations, thereby improving the strength and hardness of aluminum alloy materials; on the other hand, Ce is highly active and easy to react chemically with most metals to form a variety of refractory and hard intermetallic compounds that are very small. In aluminum alloy modification, extremely trace elements that have no strengthening effect can be converted into strengthening phases, increasing the concentration of strengthening phases and contributing to the purification of the melt.
[0010] Moreover, the Ce intermetallic compound formed is dissolved in the aluminum particles, which will cause a large lattice distortion and form high-density dislocations, hindering deformation and further ensuring strength. In the metallographic field of view, the Ce intermetallic compound generally appears as tiny white flakes, part of which is dissolved in the aluminum particles, and part of which exists in the grain boundary to form a broken chain ring, which greatly enhances the metal bond, ionic bond and van der Waals force between metals and improves the resistance to deformation.
[0011] Precisely because the strength of the modified aluminum alloy of the present application is increased, when a battery casing with certain explosion-proof requirements is subsequently prepared, the aluminum alloy of the present application can be drawn with thinner cast rods than other aluminum alloys due to its high strength, making the process simpler and easier to operate, and relatively more cost-effective.
[0012] In a possible implementation, in the aluminum alloy material, the total mass percentage of Fe and Mn is 1.75-1.95wt%, wherein the mass percentage of Fe is 0.45-0.55wt%.
[0013] The present application further ensures the strength of the aluminum alloy by controlling the iron content and the total amount of iron and manganese elements to prevent the intracrystalline segregation of the Al3Fe impurity phase and the coarse [Al(MnFe)], [Al(MnFeSi)] phases and the Mn element. Such control avoids the problem of the formation of coarse phase stress concentration points on the alloy surface caused by the difficulty in decomposing the Al3Fe impurity phase and the coarse [Al(MnFe)], [Al(MnFeSi)] phases, and further avoids the adverse effects of fatigue points, weak points, and even cracks formed when the stress concentration points are stretched multiple times, further ensuring the strength and reliability of the aluminum alloy material.
[0014] In a possible implementation, in the aluminum alloy material, the mass percentage of Cu is 0.08-0.20wt%.
[0015] In a possible implementation, in the aluminum alloy material, the mass percentage of Si is 0.18-0.70wt%.
[0016] In a possible implementation, the aluminum alloy material further includes Ti, and the mass percentage of Ti is 0.01-0.02 wt %.
[0017] This application takes into account both improving mechanical properties, preventing adhesion of hot extrusion dies and the generation of abnormal phases, controlling costs and preventing excessive small elements from poisoning the alloy. Through creative work, it is found that the Cu, Si, and Ti elements in this application are most effective within the above-mentioned mass content range, and limits are set for the Cu, Si, and Ti small elements in aluminum alloys.
[0018] In a possible implementation, the aluminum alloy material further includes Mg, and the mass percentage of Mg is less than 0.03wt%.
[0019] In a possible implementation, the aluminum alloy material further includes Cr, and the mass percentage of Cr is less than 0.10wt%.
[0020] In a possible implementation, the aluminum alloy material further includes Ni, and the mass percentage of Ni is less than 0.02wt%.
[0021] In a possible implementation, the aluminum alloy material further includes Zn, and the mass percentage of Zn is less than 0.10wt%.
[0022] In a possible implementation, the aluminum alloy material is composed of raw materials with the following mass percentages: Mn 1.25wt%, Si 0.48wt%, Cu 0.10wt%, Fe 0.55wt%, Mg<0.02wt%, Cr<0.001wt%, Ni0.004wt%, Ti 0.013wt%, Zn 0.03wt%, Ce 0.38wt%, and the balance is Al.
[0023] Through multiple sets of creative experiments, the present applicant finally found that the optimal composition ratio of each element in the aluminum alloy material is as above, which can exert excellent strength and hardness performance.
[0024] In a second aspect, the present invention provides a battery casing, wherein the casing is made of the aluminum alloy material described in the first aspect.
[0025] Since the material of the present application has high strength, good tensile strength and yield strength, the prepared battery shell can better protect the secondary battery.
[0026] In a third aspect, the present invention provides a power battery, wherein the battery comprises the battery casing according to the second aspect.
[0027] The battery casing made of the aluminum alloy of the present application is used to protect the power battery, which can meet the expectations of the power battery for aluminum alloy materials, can prevent a variety of engineering ranges, and can ensure the rigidity and thermal attenuation resistance of the battery cell.
[0028] The present application creatively adds a specific amount of Ce element to the aluminum alloy, which can refine the grains well. Compared with the low-multiple structure without adding Ce element, it can reduce the aluminum grains by one-half to one-third, which can refine the grains and effectively hinder the movement of dislocations, thereby improving the strength and hardness of the aluminum alloy material. The applicant also creatively discovered that Ce is easy to react chemically with most metals to form a variety of insoluble and hard intermetallic compounds that are very small, which can convert extremely trace elements without strengthening effects into strengthening phases, increase the concentration of strengthening phases, and further contribute to the purification of the melt. The strength, tensile strength and yield strength of the aluminum alloy modified by the present application have been significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the metallographic diagram of conventional 3003 aluminum alloy without modification.
[0030] Figure 2 This is the metallographic diagram of the aluminum alloy of Example 1 after modification of the present application.
[0031] Figure 3a -e is the metallographic diagram of the aluminum alloy of Example 2 and Comparative Examples 1-4. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the present application clearer, the technical solution of the present application will be clearly and completely described below in combination with the specific embodiments of the present application and the corresponding drawings. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
[0033] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be an intermediate element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be an intermediate element at the same time.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0035] For the specific preparation method, please refer to the following process:
[0036] 1) Mix the master alloy containing Al element (AlTi6), Mn element (AlMn10) and Fe element (AlFe10), put it into a furnace for melting, and form a uniform melt;
[0037] 2) adding an online refiner (AlTi5) to the melt obtained in step 1), controlling the amount of the addition to promote grain refinement, keeping the melt temperature stable, and stirring to ensure uniform distribution of the refiner;
[0038] 3) After step 2), the melt is refined and slag is removed to remove impurities. Argon or nitrogen is used for degassing to reduce the gas content in the melt and the possibility of porosity defects;
[0039] 4) adding a master alloy containing Ce element to the molten liquid after refining and slagging in step 3), and continuing heating and maintaining for a certain time;
[0040] 5) filtering the melt after the treatment in step 4) (eg, using a ceramic filtering device), and casting the treated melt to obtain the aluminum alloy cast rod.
[0041] 6) Extruding the aluminum alloy cast rod in step 5) to obtain an extruded profile.
[0042] In an optional process scheme, it also includes step 7) subjecting the extruded profile obtained in step 6 to homogenization annealing treatment, and subjecting the extruded aluminum alloy profile to homogenization heat treatment (annealing at about 500 degrees Celsius for 1-2 hours) to reduce segregation and improve the uniformity of the material structure.
[0043] By adopting the above method, according to the desired aluminum alloy component content, each metal raw material is weighed and prepared to obtain the following modified 3003B aluminum alloys, which are composed of the following elements in percentage by mass:
[0044] Example 1
[0045] Mn 1.25wt%, Si 0.48wt%, Cu 0.10wt%, Fe 0.55wt%, Mg<0.02wt%, Cr<0.001wt%, Ni 0.004wt%, Ti 0.013wt%, Zn 0.03wt%, Ce 0.38wt%, and the balance is Al.
[0046] Example 2
[0047] Mn 1.25wt%, Si 0.52wt%, Cu 0.10wt%, Fe 0.5wt%, Mg<0.02wt%, Cr<0.001wt%, Ni 0.004wt%, Ti 0.013wt%, Zn 0.03wt%, Ce 0.45wt%, and the balance is Al.
[0048] Example 3
[0049] Mn 1.45wt%, Si 0.32wt%, Cu 0.10wt%, Fe 0.47wt%, Mg<0.02wt%, Cr<0.001wt%, Ni 0.004wt%, Ti 0.013wt%, Zn 0.03wt%, Ce 0.47wt%, and the balance is Al.
[0050] The modified 3003B aluminum alloy and the unmodified 3003B aluminum alloy prepared in Example 1 were taken to take metallographic images. The results are ( Figure 1-Figure 2 ) shows that the unmodified 3003B aluminum alloy has uneven grain size, large grains, and uneven precipitation phases, which easily lead to problems such as reduced mechanical properties and brittleness, and have an adverse effect on the strength of the aluminum alloy. The modified 3003B aluminum alloy of Example 1 has uniform grain size and uniform precipitation phase distribution, which can improve the strength and hardness of the material and promote the plastic deformation of the material.
[0051] The modified 3003B aluminum alloy obtained above and the unmodified 3003B aluminum alloy were tested for tensile strength, yield strength and cross-sectional shrinkage / elongation respectively. The specific test methods can refer to GB / T228.1-2021 Tensile Test of Metal Materials. The results are as follows:
[0052]
[0053] It can be seen from the above experimental results that the modified 3003B aluminum alloy in the embodiment of the present application has significantly improved tensile strength and yield strength, especially the tensile strength of the 3003B aluminum alloy is increased from an average of 113 MPa to a maximum of 142 MPa, an increase of 25.7%, and the yield strength is increased from an average of 75 MPa to a maximum of 98 MPa, an increase of 30.7%. It can be seen that the embodiment of the present application has obtained an aluminum alloy with better strength.
[0054] It can be seen from the test results of cross-sectional shrinkage and elongation that the elastic modulus and toughness of the aluminum alloy in this embodiment are increased.
[0055] Comparative Example 1
[0056] The difference from Example 2 is that the addition of the Ce element is eliminated and the content is adjusted to be the balance Al.
[0057] Comparative Example 2
[0058] The difference from Example 2 is that the mass percentage of Ce element is adjusted to 0.15%.
[0059] Comparative Example 3
[0060] The difference from Example 2 is that the mass percentage of Ce element is adjusted to 0.25%.
[0061] Comparative Example 4
[0062] The difference from Example 2 is that the mass percentage of Ce element is adjusted to 1.15%.
[0063] Metallographic images were taken for Example 2 and Comparative Examples 1 to 4, and the results are as follows: Figure 3a -e as shown.
[0064] Figure 3 (a) In the aluminum alloy without Ce addition, sharp and coarse rod-shaped Al6(Mn,Fe) phases are distributed in the aluminum matrix.
[0065] In the aluminum alloys with 0.15% Ce and 0.25% Ce added in Figure 3(b) and Figure 3(c), the microstructure is still parallel thick rod-shaped Al6(Mn,Fe).
[0066] FIG3( d ) is an aluminum alloy in Example 2 with 0.45% Ce added, wherein a coarse lamellar structure is distributed on the matrix, and there are some dendrites at the edge of the structure. The overall grain size is uniform and the precipitated phase is evenly distributed.
[0067] Figure 3(e) shows that excessive addition of Ce element will cause the dendrites at the edge of the lamellar structure to grow, and the picture shows that some small white flaky structures containing cerium compounds are dispersed on the matrix.
[0068] The characteristics of the aluminum-manganese-iron phase in the 3003 aluminum alloy with excellent performance are: distributed in the aluminum alloy matrix in block or needle-shaped form, the strengthening phase should be fine-grained and evenly dispersed, and coarse phases including rod-shaped and other shapes should be avoided. Specifically, the uniformly distributed block or needle-shaped aluminum-manganese-iron phase has a relatively high hardness. Its existence contributes to the strength and hardness of the aluminum alloy, and has a relatively small effect on plasticity, reducing cracks and deformation during processing. It has high thermal stability and is not easy to decompose at high temperatures. However, if the aluminum-manganese-iron phase is too large or unevenly distributed, it may cause local stress concentration and reduce the plasticity and toughness of the alloy.
[0069] In Figure 3(a)-(c), Al6(Mn,Fe) is a coarse, sharp, rod-shaped Al6(Mn,Fe) phase, and the phase is also unevenly distributed, which will reduce the overall performance of the alloy. In Figure 3(e), the aluminum-manganese-iron phase is too large and unevenly distributed, which is also not conducive to the overall performance of the alloy. In Figure 3(d), the aluminum-manganese-iron phase is evenly distributed and is a coarse phase, and the resulting alloy has excellent performance.
[0070] In general, adding too little or too much Ce element will be detrimental to improving the strength of the aluminum alloy. Only within the content range of Ce element added specifically in this application can the effect of improving the strength of the aluminum alloy be achieved.
[0071] The above-mentioned aluminum alloy profile is further processed, the battery shell blank obtained by extrusion is put on the core rod of the cold drawing die, and the front end of the blank is extended into the cold drawing cavity of the cold drawing die, the shell blank is pulled along the drawing direction, and the core rod is moved in the same direction as the shell blank along the drawing direction, so that the shell blank is passed through the cold drawing cavity as a whole to form a battery shell.
[0072] The above-mentioned battery shell is put on the outside of the power battery body to form a power battery assembly. The protective shell of this embodiment has high strength and outstanding mechanical properties, so it can provide stronger protection for the power battery, meet the special requirements of the power battery for aluminum alloy materials under various working conditions, and improve the thermal attenuation resistance of the battery cell.
[0073] The above embodiments only express the preferred implementation modes of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An aluminum alloy material, characterized in that: The aluminum alloy material at least includes Al, Mn, Si, Cu, Fe and Ce, wherein the mass percentage of Ce is 0.3-1wt%.
2. The aluminum alloy material according to claim 1, characterized in that: In the aluminum alloy material, the total mass percentage of Fe and Mn is 1.75-1.95wt%, wherein the mass percentage of Fe is 0.45-0.55wt%.
3. The aluminum alloy material according to claim 1, characterized in that: In the aluminum alloy material, the mass percentage of Cu is 0.08-0.20wt%.
4. The aluminum alloy material according to claim 1, characterized in that: In the aluminum alloy material, the mass percentage of Si is 0.18-0.70wt%.
5. The aluminum alloy material according to claim 1, characterized in that: The aluminum alloy material also includes Ti, and the mass percentage of Ti is 0.01-0.02wt%.
6. The aluminum alloy material according to claim 1, characterized in that: The aluminum alloy material further comprises Ni, and the mass percentage of Ni is less than 0.02wt%.
7. The aluminum alloy material according to claim 1, characterized in that: The aluminum alloy material also includes Zn, and the mass percentage of Zn is less than 0.10wt%.
8. The aluminum alloy material according to claim 1, characterized in that: It is composed of the following elements in percentage by mass: Mn 1.25wt%, Si 0.48wt%, Cu 0.10wt%, Fe 0.55wt%, Mg<0.02wt%, Cr<0.001wt%, Ni 0.004wt%, Ti 0.013wt%, Zn 0.03wt%, Ce 0.38wt%, and the balance is Al.
9. A battery casing, characterized in that: The battery shell is made of the aluminum alloy material according to any one of claims 1 to 8.
10. A power battery, characterized in that: Comprising the battery casing as claimed in claim 9.
Citation Information
Cited By
Aluminum alloy material, method for manufacturing battery housing by means of cold drawing, and preparation method for aluminum alloy cast rod
WO2026113623A1